Building Criteria for Assessing the Impact of Policy on the Development of Sports for Everyone - Thi Hong Lien, MSc. Nguyen (International Journal of Humanities and Education Development (IJHED), 2022)
Based on the promulgated physical training and sport development policies, regulations on policy impact assessment, the values ​​of sport in practice, through surveys and surveys. In fact, through a poll of experts and research results, 6 groups of criteria were selected to evaluate the impact of policies on the development of sport and sport for everyone. The evaluation criteria are scientifically and realistically developed. and ensure reliability through test results by Cronbach Alpha coefficient (Internal Consistent Reliability Analysis) and exploratory factor analysis EFA (KMO and Bartlett's Test).